Lower thoracic rib stress fractures in baseball pitchers? - Gerrie, B. J.; Harris, J. D.; Lintner, D. M.; McCulloch, P. C. (The Physician and Sportsmedicine, 2015)
Stress fractures of the first rib on the dominant throwing side are well-described in baseball pitchers; however, lower thoracic rib fractures are not commonly recognized. While common in other sports such as rowing, there is scant literature on these injuries in baseball. Intercostal muscle strains are commonly diagnosed in baseball pitchers and have a nearly identical presentation but also a highly variable healing time. The diagnosis of a rib stress fracture can predict a more protracted recovery. This case series presents two collegiate baseball pitchers on one team during the same season who were originally diagnosed with intercostal muscle strains, which following magnetic resonance imaging (MRI) were found to have actually sustained lower thoracic rib stress fractures. The first sustained a stress fracture of the posterior aspect of the right 8th rib on the dominant arm side, while the second presented with a left-sided 10th rib stress fracture on the nondominant arm side. In both cases, MRI was used to visualize the fractures as plain radiographs are insensitive and commonly negative early in patient presentation. Patients were treated with activity modification, and symptomatic management for 4-6 weeks with a graduated return to throwing and competition by 8-10 weeks. The repetitive high stresses incurred by pitching may cause either dominant or nondominant rib stress fractures and this should be included in the differential diagnosis of thoracic injuries in throwers. It is especially important that athletic trainers and team physicians consider this diagnosis, as rib fractures may have a protracted course and delayed return to play. Additionally, using the appropriate imaging techniques to establish an accurate diagnosis can help inform return-to-play decisions, which have important practical applications in baseball, such as roster management and eligibility.